Dynamic radiation force of acoustic waves on absorbing spheres - Silva,Glauber T. (2010)
We present a theoretical study on how dynamic radiation force of acoustic waves actuates on absorbing spheres. We consider the radiation force is generated by the difference-frequency component of a bichromatic plane wave in a lossless fluid. We analyze the spectrum of the dynamic radiation force for polymethymethacrylate (lucite) and polyethylene spheres. Results reveal that absorption cause the appearance of resonances in the spectrum of the force. The information associated to the resonances might be useful in radiation force techniques for nondestructive material evaluation and biological tissue characterization.